Chemical characterization and insecticidal effect against Sitophilus zeamais (maize weevil) of essential oil from Croton rudolphianus leaves. (March 2020) - Ribeiro, Ingridd Ayslane Torres de Araújo; da Silva, Rosimere; da Silva, Alexandre Gomes; Milet-Pinheiro, Paulo; Paiva, Patrícia Maria Guedes; Navarro, Daniela Maria do Amaral Ferraz; da Silva, Márcia Vanusa; Napoleão, Thiago Henrique; Correia, Maria Tereza dos Santos
Abstract: The control of insect pests (such as Sitophilus zeamais ) depends mostly on the utilization of synthetic pesticides. Nevertheless, the application of these pesticides leads to many problems; environmental contamination, development of insect resistance, and adverse effects on human health are some of them. This study investigated the chemical constitution, insecticidal activity, and feeding deterrent and repellent effects on S. zeamais of essential oil (EO) obtained from Croton rudolphianus leaves. Fifty-four compounds were revealed in the C. rudolphianus oil. The major compounds of the oil consisted of an unknown compound (40.90%), methyl chavicol (22.96%), ( E )-caryophyllene (4.22%), eugenol (4.03%), bicycloelemene (3.96%), bicyclogermacrene (3.81%), and spathulenol (2.79%). The EO was toxic to S. zeamais when ingested (LC50 102.66 μL/g) and caused changes in the nutritional parameters (relative consumption rate, relative biomass gain, and efficiency of food conversion). The oil was also toxic by contact (LC50 70.64 μL/mL) and fumigation [64 μL/L in the air caused the highest mortality (43.75%)]. However, no repellent property was detected. The results of this study showed that EO from C. rudolphianus leaves is toxic in different ways to S. zeamais adults, pointing to its potential use for grain protection. Graphical abstract: Image 1 Highlights: An essential oil from Croton rudolphianus leaves induced mortality of adult Sitophilus zeamais . The oil was toxic to insects by ingestion, contact and fumigation. The oil could be useful in traps for the maize weevil due to its attractive effect.